Pembelajaran Berbasis Kontekstual (Contextual Teaching and Learning) dalam Pendidikan Agama Islam di Sekolah - Silsi Ivana Pratiwi; Agus Joko Purwanto (Jurnal Wahana Literasi Pendidikan, 2026)
The purpose of this study is to describe the components of learning, learning strategies, and the relevance and implications of contextual teaching and learning in Islamic religious education. The method used in this study is a qualitative literature review, which focuses on analyzing various literature related to contextual teaching and learning in Islamic religious education. The results of the study show that students are expected to understand the meaning of the subject matter they are learning by relating it to the context of their daily lives. This allows students to acquire knowledge and skills that are flexible and applicable. In addition, contextual teaching and learning can help educators or teachers in realizing productive and active learning by paying attention to the components and strategies of learning in Islamic religious education lessons, as well as being able to relate them through their relevance and implications.